Sublime - Lauren, Christina (New York : Simon & Schuster BFYR, 2014)
"Lucy and Colin discover they have a connection on the grounds of the private school they attend, but Lucy has a startling secret"--
Keywords: Dead -- Juvenile fiction; Ghost stories; Paranormal fiction; Man-woman relationships -- Juvenile fiction; Dead -- Fiction; Ghosts -- Fiction; Supernatural -- Fiction; Love -- Fiction